Peculiarities of electromagnetic filter operation in penning source with metal hydride cathode - Sereda, I.; Hrechko, Ya.; Babenko, Ie.; Kashaba, A. (Вопросы атомной науки и техники, 2020)
The paper describes a method of negative hydrogen ions separation from axial flow of charged particles extract- ed from Penning discharge with a metal hydride cathode. For this purpose, an electromagnetic filter has been designed basing on numerical solution of motion equations of charged particles in the filter. The optimal parameters of the filter operation were determined for the effective registration of negative hydrogen ions extracted in axial direction. Performed calculations together with experimental verification shows that there are not more than 10 % electrons in the registered Н ⁻ current. This model could be applied for the interpretation of any experiments with Н ⁻ ions separation from an axial flow of charged particles extracted from a source with cylindrical geometry. Описаний метод сепарації негативних іонів водню з аксіального потоку заряджених частинок, що виходять із розряду Пеннінга з металогідридним катодом. З цією метою на основі чисельного рішення рівняння руху заряджених частинок був розроблений електромагнітний фільтр. Визначено оптимальні параметри роботи фільтра для ефективної реєстрації негативних іонів водню, що виходять в аксіальному напрямку. Зроблені розрахунки разом з експериментальною перевіркою показали, що не більше 10% електронів реєструються в струмі негативних іонів водню. Ця модель може бути застосована для інтерпретації будь-яких експериментів по сепарації іонів Н ⁻ з аксіального потоку заряджених частинок, що витягаються з джерела, що має циліндричну геометрію. Описан метод сепарации отрицательных ионов водорода из аксиального потока заряженных частиц, выходящих из разряда Пеннинга с металлогидридным катодом. С этой целью на основе численного решения уравнения движения заряженных частиц разработан электромагнитный фильтр. Определены оптимальные параметры работы фильтра для эффективной регистрации отрицательных ионов водорода, выходящих в аксиальном направлении. Проделанные расчеты вместе с экспериментальной проверкой показали, что не более 10% электронов содержится в регистрируемом токе отрицательных ионов водорода. Данная модель может быть применена для интерпретации любых экспериментов по сепарации ионов Н ⁻ из аксиального потока заряженных частиц, извлекаемых из источника с цилиндрической геометрией.